Lyngbya Helmetica aziz a. Sp. Nov. and Scytonema Simmeri Schmidle a new record (Cyanobacteria) from Bangladesh, and their possible uses as medicines and sun screen cream - Aziz, Abdul (Bangladesh Journal of Botany, 2025)
Lyngbya helmetica Aziz sp. nov. and Scytonema simmeri Schmidle a new record from an exposed south facing yellow painted wall under intense solar radiation (≈950 µE m-2 s-1), ultraviolet exposer, high temperature (≈35° C), and severe desiccation, in Teknaf, Cox’s Bazar, Bangladesh, Both the taxa formed dark compact patches composed of narrow filaments enriched with sheath-associated pigments, in addition to scytonemin and granular vermilion around the trichome. In L. helmetica, degradation of terminal trichome cells produced electrochemical biosensors those causes extensions of both outer and inner sheath tip interiorly forming outer and inner ‘helmet’ like protective structures retaining all the pigments inside. S. simmeri exhibited comparable protective responses through closing the sheath opening. UV rays and heat disrupt heterocyst–trichome connections. Microscopic observations indicate that sheath modification and pigment impregnation are key morphological adaptations facilitating survival on the desiccated wall. This study provides the formal description of L. helmetica sp nov., reports S. simmeri as a new record for Bangladesh, and documented stress induced sheath adaptations through electrochemical biosensors in cyanobacteria. Bangladesh J. Bot. 54(4): 885-890, 2025 (December)